A Perspective on Frailty and its Predisposing Factors among People Living with HIV - Morante-Ruiz, Miguel; Sanabria-Girón, Paulo César; Rubio-Martín, Rafael; Cervantes-Pérez, Enrique; Seager, Anna; Míguez-Arrúa, Julieta; Cabello-Úbeda, Alfonso (Current HIV Research, 2024)
People Living with HIV (PLHIV) experience accelerated aging, yet strategies for healthy aging in this group are not well studied. Although survival rates have improved, non-infectious comorbidities, like cardiovascular diseases, diabetes, and cancers, are increasing and tend to appear earlier and more severely in PLHIV frailty, defined as increased vulnerability to stressors, which is a growing concern among aging PLHIV, driven by factors, like chronic inflammation, antiretroviral therapy toxicity, and traditional risk factors. Key areas of focus include inactivity, sarcopenia, vitamin D deficiency, and polypharmacy. Addressing these factors is crucial to preventing functional decline and improving the quality of life of PLHIV, though more research is necessary. The aim of this article was to identify and conduct a narrative review of these factors in a pragmatic way in order to facilitate the clinicians.
Keywords: polypharmacy